MANAJEMEN PELAYANAN PUBLIK PADA PDAM KOTA PEKANBARU - Arliliwati "; Febri Yuliani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Anticipated PDAM Kota Pekanbaru service management in general have not been able to meet the needs of customers well. Technical constraints, especially lack of funds,congestion water delivered, the water is not clear other than that the demage to pipes, drains and Administrative services convoluted in the PDAM Kota Pekanbaru. Supposedly this PDAM Kota Pekanbaru as a company that is trusted by the city government to meet the needs of society pekanbaru,PDAM Kota pekanbaru will be able to realize the goal of clean water of company. The problem in this research is how the conditions of service management at PDAM Kota Pekanbaru in realizing it’s objectives and the factors that affect the service management. The concept is the theory that researchers use PDAM Kota Pekanbaru service management, this study used qualitative research methods to study descriptive data. In collecting the data, researchers use interviewing techniques, observation and documentation. By using key informants as sources of information and literatures. These result indicate that the conditions of service management PDAM Kota Pekanbaru are in the category of not yet effective, which it is seen from city taps away goal achievement PDAM Kota Pekanbaru. Factors that affect the service management this PDAM Kota Pekanbaru there are, human resources, facilities and technology, costs, service personel competence, service time, the duty and authority of employees, employee performance, and coaching employees, which to all of these factors are very influential and must be in line for service management in PDAM Kota Pekanbaru. Key Word: Service Management Of PDAM Kota Pekanbaru